Evaluation of a digital patient education programme in patients with coronary artery disease, a survey-based study - Anna Sandberg; Annica Ravn-Fischer; Annika Johnsson; Maria Lachonius; Maria Bäck (BMC, 2024)
Abstract Introduction Patient education programmes focusing on risk factor modification and lifestyle changes are well established as part of cardiac rehabilitation in patients with coronary artery disease (CAD). As participation rates are low, digital patient education programmes (DPE) are interesting alternatives to increase access. Understanding patients' perceptions of DPE are important in terms of successful implementation in clinical practice but are not well known. Therefore, the aim of this study was to assess patients' perceptions of using a DPE in terms of end-user acceptance and usability, perceived significance for lifestyle changes and secondary preventive goal fulfilment in patients with CAD. Methods This was a cross-sectional survey-based study. The survey was distributed to all 1625 patients with acute coronary syndrome or chronic CAD with revascularisation, who were registered users of the DPE between 2020 and 2022 as part of cardiac rehabilitation. The survey contained 64 questions about e.g., acceptance and usability, perceived significance for making lifestyle changes and secondary preventive goal fulfilment. Patients who had never logged in to the DPE received questions about their reasons for not logging in. Data were analysed descriptively. Results A total of 366 patients (mean age: 69.1 ± 11.3 years, 20% female) completed the survey and among those 207 patients (57%) had used the DPE. Patients reported that the DPE was simple to use (80%) and improved access to healthcare (67-75%). A total of 69% of the patients were generally satisfied with the DPE, > 60% reported that the DPE increased their knowledge about secondary preventive treatment goals and approximately 60% reported having a healthy lifestyle today. On the other hand, 35% of the patients would have preferred a hospital-based education programme. Among the 159 patients (43%) who had never used the DPE, the most reported reason was a perceived need for more information about how to use the DPE (52%). Conclusions This study shows an overall high level of patient acceptance and usability of the DPE, which supports its continued development and long-term role in cardiac rehabilitation in patients with CAD. Future studies should assess associations between participation in the DPE and clinical outcomes, such as secondary preventive goal fulfilment and hospitalisation.